HARMONIZATION OF PROTECTION PRINCIPLES OF MIGRAN WORKERS’ RIGHT TO HEALTH IN THE EFFORT OF ASEAN UNIVERSAL HEALTH COVERAGE IMPLEMENTATION - Muhammad Asphian Arwin; Aktieva Tri Tjitrawati (Jurnal Dinamika Hukum, 2018)
Millions of workers migrate within ASEAN countries each year. Malaysia, Singapore, Thailand and Brunei Darussalam as recipient countries while Indonesia, Philippines, Thailand, Cambodia, Laos and Vietnam as senders of migrant workers. Migrants, who work in both formal and informal sectors, play important roles to increase national income for both sender and recipient countries, unfortunately, they lack of welfare distribution including health insurance by both countries. This research is aimed to find an alternative solution to the problem by proposing the concept of UHC implementation in ASEAN. In the context of ASEAN law, all ASEAN people could enjoy rights of health insurance from ASEAN countries. This research is a normative research, using conceptual and statute approach. The result of the analysis is expected to generate concepts which can be underlying the arrangement of public health insurance in ASEAN countries, subsequently, to be used as material for drafting the ASEAN UHC. Keywords: protection principle, migrant workers, health care